2016
DOI: 10.1097/shk.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of PCSK9 Modulates Infection, Inflammation, and Coagulation in a Murine Model of Sepsis

Abstract: These findings demonstrate that PCSK9 deficiency confers protection against systemic bacterial dissemination, organ pathology, and tissue inflammation, particularly in the lungs and liver, while PCSK9 overexpression exacerbates multi-organ pathology as well as the hypercoagulable and pro-inflammatory states in early sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 39 publications
5
106
0
Order By: Relevance
“…The results of a recent in vivo study conducted by Dwivedi et al () who investigated the effects of differential PCSK9 expression on sepsis and inflammation were consistent with these findings. The results of this study suggest that, during induced sepsis, PCSK9 overexpression promotes bacterial dissemination, multiple organ failure, and tissue inflammation while reduced expression of PCSK9 suppresses systemic bacterial dissemination, organ damage, and inflammatory response.…”
Section: Role Of Pcsk9 In Sepsis and Septic Shocksupporting
confidence: 77%
“…The results of a recent in vivo study conducted by Dwivedi et al () who investigated the effects of differential PCSK9 expression on sepsis and inflammation were consistent with these findings. The results of this study suggest that, during induced sepsis, PCSK9 overexpression promotes bacterial dissemination, multiple organ failure, and tissue inflammation while reduced expression of PCSK9 suppresses systemic bacterial dissemination, organ damage, and inflammatory response.…”
Section: Role Of Pcsk9 In Sepsis and Septic Shocksupporting
confidence: 77%
“…Dyspnoea, cyanosis, and overall grimace scores were increased in septic mice overexpressing PCSK9 relative to WT controls. Notably, bacterial load was significantly reduced in PCSK9 KO mice, showing also protection against systemic bacterial dissemination (Dwivedi et al, ). Similarly, it has been reported that humans carrying loss‐of‐function variants of the PCSK9 gene have increased survival during sepsis (Walley, ).…”
Section: Pcsk9 and Infectionsmentioning
confidence: 99%
“…This benefit endures; PCSK9 LOF patients had significantly lower rates of readmission or death after sepsis [71]. In a clinically relevant murine model of sepsis, we showed that: (1) PCSK9 knockout mice and (2) mice treated 6 h after the induction of peritonitis with a PCSK9-blocking antibody had a higher survival rate and lower inflammatory responses [57]. The therapies discussed in this section are summarized in Table 1.…”
Section: Personalized Medicine For Sepsismentioning
confidence: 99%
“…Furthermore, in humans, PCSK9 loss of function genotype was associated with increased 28-day survival (compared with the wild-type genotype) in 2 cohorts of patients with septic shock [56]. In an animal model of sepsis, PCSK9 knockout mice subjected to cecal ligation and puncture had lower bacterial concentrations in the blood, lungs, and peritoneal fluid than wild-type controls; PCSK9-overexpressing mice had higher bacterial concentrations in the blood, lungs, and peritoneal fluid [57]. Thus, the inhibition of PCSK9 has several potentially beneficial effects in sepsis and septic shock: (1) it increases hepatic clearance of pathogen endotoxins by increasing LDLR expression, and (2) it decreases the bacterial load in the peritoneum and, remarkably, also at remote sites (blood and lung).…”
Section: Management Of Organism and Organism Toxicity In Septic Shockmentioning
confidence: 99%